2020
DOI: 10.31234/osf.io/c3vsr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19: A Boon or a Bane for Creativity?

Abstract: In many countries, the COVID-19 pandemic led to a period of lockdown that impacted individual’s lifestyles, in both professional and personal spheres. New problems and challenges arose, as well as opportunities. Numerous studies have examined the negative effects of lockdown measures, but few have attempted to shine light on the potential positive effects that may come out of these measures. We focused on one particular positive outcome that might have emerged from lockdown: creativity. To this end, this paper… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
(61 reference statements)
2
6
2
Order By: Relevance
“…Creativity changes were first estimated based on a self-report of a change as perceived by each participant (SCC). SCC revealed that participants experienced being more creative during the lockdown than the period before, which is consistent with previous studies that reported an increase in everyday creativity during the lockdown 32,33 . SCC correlated with the BFI-O score, which captures a basal creative personality trait 38,39 and which was in the range of what has been previously observed 40 .…”
Section: Creativity During the Lockdownsupporting
confidence: 91%
See 2 more Smart Citations
“…Creativity changes were first estimated based on a self-report of a change as perceived by each participant (SCC). SCC revealed that participants experienced being more creative during the lockdown than the period before, which is consistent with previous studies that reported an increase in everyday creativity during the lockdown 32,33 . SCC correlated with the BFI-O score, which captures a basal creative personality trait 38,39 and which was in the range of what has been previously observed 40 .…”
Section: Creativity During the Lockdownsupporting
confidence: 91%
“…The link between BFI-O and SCC was linear: the increase in self-perceived creativity was proportional to the BFI-O score. This last result seems at variance with Mercier and colleagues' 32 results showing that participants with a lower creativity baseline experienced a larger improvement in everyday creativity during the lockdown than those with a higher baseline. Their baseline measure of creativity was assessed by adapting a past tense scale of everyday situations.…”
Section: Creativity During the Lockdowncontrasting
confidence: 64%
See 1 more Smart Citation
“…COVID-19 devastates not only our health but also economies, including creative professions (Comunian and England, 2020 ). While its effects on everyday creativity are less established (but see Mercier et al, 2021 ), there is a growing number of studies that lead us to infer that even thinking about the threat associated with the recent pandemic is harmful to creative thinking and problem-solving (Karwowski et al, 2020 ). But does it apply to creative activity as well?…”
Section: Discussionmentioning
confidence: 99%
“…Little-c mini-c (Kaufman & Beghetto, 2009) Little-C mini-c little-c , 2018; Richards, 2007). Conner, De Young & Silvia ( Big-C ;Aznar, Sowden, Bayless, Ross, Warhurst & Pachi, 2021( Mercier et al,2021) (Baer & McKool, 2009;Barbot, Besançon & Lubart, 2011;Blamiresa & Peterson, 2014;Kaufman, Baer, Cole & Sexton, 2008 (Kaufman, Lee, Baer & Lee, 2007; ; Krumm, Lemos & Filippetti, 2014;Park et al, Palmon & Kaufman, (2012) 2016) (Baer & McKool, 2009;Kaufman et al, 2007) (Blamiresa & Peterson, 2014 item response theory (IRT) Generalized Partial Credit Model (GPCM; Ostini & Nering, 2006) ‫المجموعات‬ ‫؟‬ ‫البحث:‬ ‫أهداف‬ ‫اليومي‬ .…”
mentioning
confidence: 99%